LOGISTICS SUPPORT SYSTEM OF THE ARMED FORCES OF UKRAINE IN WARTIME CONDITIONS - Melnyk , Valentyn; Kuvshynova , Oksana (Collection of scientific papers «ΛΌГOΣ», 2025)
Logistics support plays a key role in modern warfare, and for the Armed Forces of Ukraine (AFU) it is a crucial factor in combat effectiveness. The uninterrupted supply of ammunition, equipment, fuel, food, medical supplies and other resources determines the speed of response, the manoeuvrability of troops and the ability to hold positions.